BIOMIMETIC HYDROLYSIS OF CELLULOSE TO GLUCOSE - Abdillah, Fauziah
Glucose is a basic chemical that has many derivative products. Glucose can be obtained from the hydrolysis of cellulose. Active site of cellulase enzyme, a natural cellulose hydrolyzer, contains a pair of carboxylic groups, provided by protein residue of glutamic acid/aspartic acid. This study aims to understand the effectiveness of glutamic acid, piperazinium dihydrogen sulfate and piperazine dihydrochloride, all having diacid characteristic whose structure mimic the diacid in cellulase enzyme’s active site, as a catalyst for hydrolysis of cellulose, combined with transition metal salts, Mn(II) sulfate and Cr(III) sulfate as agents for refducing cellulose crystallinity. Hydrolysis was carried out in the aqueous phase, with temperatures of 50?C and 100?C. The results of this research showed that combinations of piperazinium dihydrogen-sulfate/dihidrochloride/dioxalate + Mn(II) [atau Cr(III)] sulfate are quite satisfying cellulose hydrolysis catalyst + decrystalisation agent; at very mild conditions, temperature 100oC, relatively low concentrations of both the catalysts (12,2 mM) dan the decristalysation agent (0,31 – 0,46 mM), a hydrolysis time of 3 hours already achieved 10% degree of hydrolysis. Therefore, catalyst of the type dioxalate/dihydrogen sulfate/dihidrochloride of organic diamine compounds need further research and development to put into reality their potential as biomimetic catalysts for hydrolyzing cellulose.